Pentahelix Model in Community Based Tourism Development: Roles, Challenges, and Synergy Enhancement - Pane, Rico Purnawandi; Nasution, Hazqon Fuadi; Susanto, Agus; Rafi, M.; Fatmawati, Fatmawati (Lasigo Akademia Indonesia, 2025)
Community Based Tourism (CBT) is a key strategy for sustainable tourism development, particularly in areas rich in natural and cultural resources such as North Rupat Sub-District, Bengkalis Regency. Despite its designation as a National Tourism Strategic Area, CBT implementation in North Rupat continues to face challenges including inconsistent community participation, limited mentoring, and weak program sustainability. This study employs a qualitative approach within the pentahelix framework government, academia, business, community, and media to analyze stakeholder roles in tourism development. Data were collected through in-depth interviews with eight purposively selected informants directly involved in tourism activities, supported by participant observation and documentation. Data were analyzed using the Miles and Huberman interactive model through stages of data reduction, presentation, and conclusion drawing. The findings reveal that while all actors contribute to tourism development, weak coordination and limited long-term mentoring hinder the effectiveness and sustainability of CBT initiatives. This study contributes by applying the pentahelix collaboration model to the context of North Rupat for the first time, integrating it with the concept of community based tourism. Strengthening community capacity, adaptive governance, and cross-sector collaboration is essential to achieving sustainable tourism development and inclusive local economic growth.